Form of phosphate enrichment of the CaO base containing V2O5 and TiO2 semi-steel slag - WANG Bao-hua; LIU Chong; ZHU Rong; ZHANG Ming-bo; CHENG Yu-jun; HAN Yu (工程科学学报, 2018)
Studying on the Ca O base containing V2O5and Ti O2semi-steel slag, a model of enrichment degree Rci-cjwas built with the help of the ion and molecule coexistence theory, the result was compared with the actual enrichment form of phosphate.The results indicate that with the increasing of basicity, the mass action concentration of 3CaO·P2O5gradually decreases, and the mass action concentration of 4CaO·P2O5gradually increases.While the mass action concentration of 2CaO·Si O2first increases and then decreases.The enrichment possibility range of the C3P+C4P is 87%-94%and the C2S that is the essential substance for the formation of the rich phosphate mineral phase is main calcium silicate compounds.The solid solution 2CaO-Si O2-3CaO-P2O5 (C2S-C3P) and 2CaO-Si O2-4CaO-P2O5 (C2S-C4P) are the primary phosphate enrichment phase in the slag.According to the scanning electron microscopy (SEM) results, X-ray diffraction (XRD) analysis and hypothesis, the containing P2O5solid solution in dark grey area is calculated as2CaO·Si O2-3CaO·P2O5and 2CaO·Si O2-4CaO·P2O5, which is consistent with the theoretical calculation results.